2017
DOI: 10.1111/neup.12399
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy case of Creutzfeldt‐Jakob disease with a prion protein gene codon 180 mutation presenting with pathological laughing and an exaggerated startle reaction

Abstract: A 78-year-old Japanese woman presented with slow progressive disorientation and memory disturbances. Pathological laughing was observed at an early disease stage and continued for several months. Around the same time, the patient began to exhibit an exaggerated startle reaction and mild myoclonus. The pathological laughing and startle reaction disappeared before the patient reached an akinetic mutism state approximately 16 months after symptom onset. MRI showed extensive hyperintensity of the cerebral cortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 22 publications
(101 reference statements)
4
42
1
Order By: Relevance
“…The diagnosis of CJD in the present case was suspected based on MRI findings in the early disease stage. Previous reports have indicated that V180I gCJD cases exhibit a characteristic finding as if the cerebral cortex is swelling in T2‐weighted and FLAIR images, as well as widespread cortical hyperintensity on DWI, except for the medial occipital and cerebellar cortices . We speculate that these typical MRI findings may also provide a rationale for clinically suspecting V180I gCJD prior to performing PrP gene analysis.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…The diagnosis of CJD in the present case was suspected based on MRI findings in the early disease stage. Previous reports have indicated that V180I gCJD cases exhibit a characteristic finding as if the cerebral cortex is swelling in T2‐weighted and FLAIR images, as well as widespread cortical hyperintensity on DWI, except for the medial occipital and cerebellar cortices . We speculate that these typical MRI findings may also provide a rationale for clinically suspecting V180I gCJD prior to performing PrP gene analysis.…”
Section: Discussionmentioning
confidence: 51%
“…In the present case, diffuse vacuoles in the cerebral cortex were observable macroscopically by loupe on the images of HE‐stained tissue. VaSNoC‐type vacuoles are visually different from the “fine vacuoles” observed in MM1‐type sCJD, as well as from the “large confluent vacuoles” observed in MM2‐cortical type sCJD . The appearance of VaSNoC‐type vacuoles in the cerebral cortex is considered a feature of V180I gCJD .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations